Fifty Cents and a Dream - Asim, Jabari 1962-; Collier, Bryan (New York : Little, Brown and Co., 2012)
A biography of the former slave and inspiring educator describes the hardships he overcame in youth, the circumstances that challenged his efforts to learn how to read, and his triumphant pursuit of a college education.
Keywords: Washington, Booker T., -- 1856-1915; African Americans -- Biography; Educators -- Biography -- United States